Embodying character education values: "Malin Kundang" and community character development - F. Ferdinal; O. Oktavianus (Journal of Community Service and Empowerment, 2024)
Intangible heritage, such as folklore, plays a crucial role in preserving cultural values and traditions. Regular efforts are needed to ensure these stories, and their embedded values are passed down through generations. Many ways can be conducted, including socialization and implementation of character education values. This article aims to socialize and implement the character education values contained in folklore. This community service program is an attempt to preserve and pass down the character education values contained in the legend "Malin Kundang," a well-known legend about a son's disobedience to his mother and cursed to be a stone, to many segments of people, especially youngsters in West Sumatra and its surroundings. Unversitas Andalas lecturers and students in Sumatra Barat, Sumatra Selatan, Bengkulu, and Riau conducted the program. We collected data regarding people's knowledge of "Malin Kundang," its educational values, and the methods of sustaining the values for the next generation. The results show that 65 out of 79 (82%) respondents understand the legend "Malin Kundang." Sixty-seven (85%) respondents agree that religious, moral, and social values such as courtesy, respect for others, obedience to parents, hard work, abstinence, and remembrance of origin are values to be passed on to others. While 'Malin Kundang' is widely known, continuous efforts are needed to instill its values in the younger generation. Utilizing modern techniques such as IT and media can enhance the preservation and dissemination of these cultural values.